THE PHENOMENON OF DIGLOSIA BETWEEN SUNDAN LANGUAGE AND JAVANESE LANGUAGE AT SMAN 1 CIGALONTANG AND DARUL MUTA'ALLIMIN ISLAMIC BOARDING SCHOOL - Lisa Herlina; Jein Fitria Sriwulan Pitaloka; Ichsan Fauzi Rahman (Media Inovasi Pendidikan dan Publikasi, 2024)
Sociolinguistics is the study or discussion of language in relation to its speakers as members of society. Diglossia is a linguistic phenomenon where a society uses two different languages ​​in its daily life: a high variety and a low variety. High variance is usually used in formal situations such as government, media, and education, while low variance is used in informal situations such as everyday conversation. In terms of daily conversation, the diglossia system can have a very prominent impact on change due to environmental factors. We researched this by interviewing several students from the Darul Muta'allimin Islamic Boarding School. Then, from an educational perspective, the Diglosia system can have a significant impact on language teaching in schools and student academic achievement at SMAN 1 Cigalontang. This research uses a qualitative method with a narrative research approach that focuses on individual research, using the interview method. This diglossia affects education and has an impact on students' academic achievement.